Alzheimer's disease and amyloid β-peptide deposition in the brain: a matter of 'aging'?. (22nd March 2010) - Moro, Maria Luisa; Collins, Matthew J.; Cappellini, Enrico
Abstract : Biomolecules can experience aging processes that limit their long-term functionality in organisms. Typical markers of protein aging are spontaneous chemical modifications, such as AAR (amino acid racemization) and AAI (amino acid isomerization), mainly involving aspartate and asparagine residues. Since these modifications may affect folding and turnover, they reduce protein functionality over time and may be linked to pathological conditions. The present mini-review describes evidence of AAR and AAI involvement in the misfolding and brain accumulation of Aβ (amyloid β-peptide), a central event in AD (Alzheimer's disease) synaptic dysfunctions. Structural alterations introduced by site-specific modifications linked to protein aging may affect Aβ production, polymerization and clearance, and therefore play a pivotal role in the pathogenesis of sporadic and genetic forms of AD. Early changes associated with molecular aging also have significant long-term consequences for Aβ folding and turnover. New fast, reproducible and accurate methods for the screening of protein aging markers in biological samples may contribute to improve diagnostic and therapeutic approaches in AD.